SPATIAL MULTI-CRITERIA DECISION MAKING FOR DELINEATING AGRICULTURAL LAND IN JAKARTA METROPOLITAN AREA’S HINTERLAND: CASE STUDY OF BOGOR REGENCY, WEST JAVA - Widiatmaka, Widiatmaka; Ambarwulan, Wiwin; Sudarsono, Sudarsono (AGRIVITA Journal of Agricultural Science, 2016)
The hinterland of Jakarta has experienced high pressure in its land utilization due to Jakarta’s rapid development. The objective of this research was to analyse the suitable land available for agriculture. The research was conducted in Bogor, a hinterland regency of Jakarta. The methodology used includes two steps of analysis, which are land suitability and land availability analysis. Land suitability for agriculture was analysed using multi-criteria decision making method. Seven (7) criteria were included, which consist of soil class, land capability class, slope, elevation, slope aspect, land use/land cover and distance to roads. The criteria were weighted using the Analytical Hierarchy Process. Combining criteria weights and sub-criteria scores, an overlay model in Geographic Information System was applied. The result from land suitability analysis was used as a feed for determining land availability, considering the forest area status and land allocation in the official spatial land use plan. The results indicate that an area amounting to 87.5% of Bogor Regency is suitable for agriculture. Land which is suitable and available for agriculture is 16.7% of the regency’s area. Considering available land which is currently in use, the area that can be allocated for the expansion of agriculture is 3.3%.